1995
DOI: 10.1161/01.cir.92.10.2855
|View full text |Cite
|
Sign up to set email alerts
|

N -Acetylcysteine in Combination With Nitroglycerin and Streptokinase for the Treatment of Evolving Acute Myocardial Infarction

Abstract: NAC in combination with NTG and streptokinase appeared to be safe for the treatment of evolving AMI and was associated with significantly less oxidative stress, a trend toward more rapid reperfusion, and better preservation of left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 56 publications
3
97
0
6
Order By: Relevance
“…The antioxidant and vasodilatory effects of NAC may have directly influenced subsequent mortality in these patients with cardiac disease. More specifically, NAC administration in patients with AMI has been associated with diminished oxidative stress, more rapid coronary reperfusion, preservation in ventricular function, and a decrease in the size of infarct (14,15). Furthermore, the incidence of CIN was somewhat higher than expected given the relatively preserved renal function of the study population and a 15% prevalence of diabetes.…”
Section: Randomized Clinical Trialsmentioning
confidence: 85%
“…The antioxidant and vasodilatory effects of NAC may have directly influenced subsequent mortality in these patients with cardiac disease. More specifically, NAC administration in patients with AMI has been associated with diminished oxidative stress, more rapid coronary reperfusion, preservation in ventricular function, and a decrease in the size of infarct (14,15). Furthermore, the incidence of CIN was somewhat higher than expected given the relatively preserved renal function of the study population and a 15% prevalence of diabetes.…”
Section: Randomized Clinical Trialsmentioning
confidence: 85%
“…However, it is also used for the diseases of the lungs, liver, heart, and kidney in order to treat their toxic and ischemic injuries [22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of attenuation of renal injury with N-acetylcysteine is believed to be the scavenging of oxygen-derived free radicals in the renal tubule, which is similar to the mechanism of sodium bicarbonate. 25,26 Miner et al previously reported that N-acetylcysteine reduced contrast-induced nephropathy but not clinical events (death, myocardial infarction, dialysis, hospitalization) during 9 months of follow-up. 27 A discrepancy in longterm clinical outcomes between this previous study and the present study may partially be explained by the difference in study populations.…”
Section: Effect Of Other Preventive Therapy For Contrast-induced Nephmentioning
confidence: 99%